(untitled) (Lantanida Journal, 2023)
The matoa plant (Pometia pinnata) is known as a medicinal plant that has high antioxidant activity. Cigarette smoke produces free radicals and causes oxidative stress, a condition where the number of free radicals in the body exceeds the capacity to neutralize them. The aim of this study was to evaluate the levels of malondialdehyde (MDA), superoxide dismutase (SOD) and histopathological features of rat’s lung exposed to cigarette smoke and matoa peels extract. The research method uses laboratory experimental studies using rats as research subjects. The design used was Randomized Posttest Only with Control Group Design. 24 male white rats of the wistar strain were divided into 6 groups: normal, negative control, positive control, and group I, II, III were given matoa peels extract 3, 6, and 12 mg/kgBW respectively and exposure to cigarette smoke for 14 days. After 14 days, MDA, SOD and histopathological picture of the rats’ lungs will be compared based on the group. Data analysis was carried out using a one-way ANOVA test. The results showed that matoa peels extract could reduce MDA levels and increase SOD activity in rats exposed to cigarette smoke (p value <0.05). Group that is given matoa peels extract 12 mg/kgBW can reduce lung tissue damage.